More of Dedekind: His Series Test in Normed Spaces - Robert Kantrowitz; Michael M. Neumann (International Journal of Mathematics and Mathematical Sciences)
Dedekind’s test for infinite series has a canonical interpretation in the context of normed spaces. It is shown that his test holds in a normed space precisely when the space is complete.